Phanerogamic Botanical Collections (S) - Johannes Lundberg (Swedish Museum of Natural History, 2010)
This database contains information on the specimens in the Phanerogamic Botanical Collections of the Swedish Museum of Natural History.
Keywords: Occurrence; Specimen; Occurrence; OCCURRENCE; Biological Sciences; Biologi